Upaya Penegakan Hukum Terhadap Pengguna Jasa dalam Praktik Prostitusi di Jakarta - Vidontha Kaban, Rayneld K; Firmansya, Hery (Universitas Ekasakti, 2023)
Law enforcement in criminal acts of prostitution in Indonesia is contained in various laws, both in the Criminal Code and the Pornography Law, where the penalties incurred/present for criminal acts related to prostitution are deemed disproportionate, only burdening prostitution service providers. and prostitution itself. This research uses normative-empirical legal research. Currently, law enforcement against users of prostitution services can only occur if the person is/has been married, while law enforcement against service providers and prostitution itself does not have similar conditions, so that there is no proportionality in the offenses related to prostitution itself, so that does not reflect a sense of justice for those involved, and there is no strict prohibition and punitive sanctions that can clearly threaten perpetrators who use prostitution services.